Epic voyages : Magellan, Cook, Shackleton, Heyerdahl, Chichester - Mundy, Robyn (Epic adventure., 2010)
Recounts the stories of five epic mariners who set off on some of the greatest ocean journeys ever undertaken and introduces the challenges of life at sea.